Age- and Sex-Specific Gut Microbiota Signatures Associated with Dementia-Related Brain Pathologies: An LEfSe-Based Metagenomic Study - Sun Hwa Hong; Hyun Woong Roh; You Jin Nam; Tae Wi Kim; Yong Hyuk Cho; Sang Joon Son; Chang Hyung Hong (Brain Sciences)
Background/Objectives: Emerging evidence suggests that gut microbiota composition is influenced by both age and sex and may contribute to dementia-related brain pathologies. However, comprehensive microbiome-based biomarker discovery stratified by these factors remains limited. Methods: We performed a metagenomic analysis of the gut microbiota of participants stratified by sex (female vs. male) and age (<75 vs. ≥75 years). Alpha diversity (observed operational taxonomic unit, Chao1, Shannon, and Simpson) and linear discriminant analysis effect size analyses were conducted to identify dominant taxa associated with Alzheimer’s pathology, vascular pathology, and dementia-related structural brain changes. Results: Females and non-elderly participants (aged < 75 years) exhibited higher gut microbial diversity, characterized by an increased abundance of Bifidobacterium spp. and Blautia spp., whereas males and elderly participants (aged ≥ 75 years) exhibited increased levels of Bacteroides spp. and Bacteroidia, which have been associated with inflammation and dysbiosis. Several taxa, including Bifidobacterium spp. were consistently identified as potential protective biomarkers, while Bacteroides spp. was linked to a higher risk of dementia-related brain pathologies. Conclusions: Our findings demonstrate distinct age- and sex-specific differences in gut microbiota composition that may be closely associated with the pathophysiology of dementia-related brain pathologies. These results demonstrate that gut microbiota may serve as potential biomarkers for monitoring cerebrovascular conditions, potentially contributing to the development of personalized therapeutic strategies.